Akuntabilitas Pemerintahan Desa Dalam Pengelolaan Anggaran Pendapatan Dan Belanja Desa Berdasarkan Permendagri Nomor 20 Tahun 2018 (Studi Kasus di Desa Nambangan, Kecamatan Grabag, Kabupaten Purworejo) - Anggraretha Mishwa Damayanti; Ketut Bayagkara (Jurnal Riset Akuntansi, 2023)
The village is the smallest institution in the government system of the Unitary State of the Republic of Indonesia. The people, especially the system of people's government, plays an important role in development, because people's government can be a determining factor for the success or failure of the central government in strengthening and prospering its people. The purpose of this study was to analyze the process of planning, using, administering, and reporting the Budget and Income and Expenditures (APBDes) in Nambangan Village, Grabag District, Purworejo Regency. The research method used is qualitative research with a case study approach. Data obtained through interview techniques, observation and documentation. The results of the research show that the planning, use, administration, and reporting processes are in accordance with the Minister of Home Affairs Regulation Number 20 of 2018 (PERMENDAGRI Number 20 of 2018) concerning APBDes Management. Suggestions that can be given are that the Nambangan Village Government should continue to improve access to information regarding the realization of APBDes fund allocations by making improvements and updating the content of the Nambangan Village website. This is important because it is unfortunate that the web page is currently not up to date in presenting relevant information.